Chitosan–Pluronic nanoparticles as oral delivery of anticancer gemcitabine: preparation and in vitro study - Ostad SN (Dove Medical Press, 2012)
Hosniyeh Hosseinzadeh1, Fatemeh Atyabi1, Rassoul Dinarvand1, Seyed Naser Ostad21Nanotechnology Research Centre, 2Department of Toxicology and Pharmacology, Faculty of Pharmacy, Tehran University of Medical Sciences, Tehran, IranAbstract: Nanoparticles have proven to be an effective delivery system with few side effects for anticancer drugs. In this study, gemcitabine-loaded nanoparticles have been prepared by an ionic gelation method using chitosan and Pluronic® F-127 as a carrier. Prepared nanoparticles were characterized using dynamic light scattering, Fourier transform infrared spectroscopy (FT-IR), differential scanning calorimetry (DSC), scanning electron microscopy, and transmission electron microscopy. Different parameters such as concentration of sodium tripolyphosphate, chitosan, Pluronic, and drug on the properties of the prepared nanoparticles were evaluated. In vitro drug release was studied in phosphate-buffered saline (PBS; pH = 7.4). The cytotoxicity of the nanoparticles was assayed in the HT-29 colon cancer cell line. The mucoadhesion behavior of the nanoparticles was also studied by mucus glycoprotein assay. The prepared nanoparticles had a spherical shape with positive charge and a mean diameter ranging between 80 to 170 nm. FT-IR and DSC studies found that the drug was dispersed in its amorphous form due to its potent interaction with nanoparticle matrix. Maximum drug encapsulation efficiency was achieved at 0.4 mg/mL gemcitabine while maximum drug loading was 6% obtained from 0.6 mg/mL gemcitabine. An in vitro drug release study at 37°C in PBS (pH = 7.4) exhibited a controlled release profile for chitosan–Pluronic® F-127 nanoparticles. A cytotoxicity assay of gemcitabine-loaded nanoparticles showed an increase in the cytotoxicity of gemcitabine embedded in the nanoparticles in comparison with drug alone. The mucoadhesion study results suggest that nanoparticles could be considered as an efficient oral formulation for colon cancer treatment.Keywords: chitosan, nanoparticles, ionic gelation, gemcitabine, mucoadhesion, oral drug delivery, anticancer